Anaesthetists stress is induced by patient ASA grade and may impair non‐technical skills during intubation. Issue 7 (4th March 2016) - Doleman, B.; Blackwell, J.; Karangizi, A.; Butt, W.; Bhalla, A.; Lund, J. N.; Williams, J. P.
Abstract : Background: The aims of this study were to determine if patient ASA grade was associated with increased stress in anaesthetists with a subsequent effect on non‐technical skills. Methods: Stress was measured using a validated objective (heart rate variability or heart rate) and subjective tool. We studied eight consultant anaesthetists at baseline (rest) and during 16 episodes of intubation with an ASA 1 or 2 patient vs. an ASA 3 or 4 patient. The primary outcome for the study was objective and subjective stress between both patient groups. Secondary outcomes were non‐technical skill ratings and the association between stress measurements. Results: ASA 3 or 4 patients were associated with increases in objective stress when compared to baseline (mean 4.6 vs. 6.7; P = 0.004). However, ASA 1 or 2 patients were not associated with increases in stress when compared to baseline (mean 4.6 vs. 4.7; P = 1). There was no significant difference in subjective stress between the groups ( P = 0.18). Objective stress negatively affected situational awareness ( P = 0.03) and decision‐making ( P = 0.03); however, these did not decline to a clinically significant threshold. Heart rate variability ( r = 0.60; P = 0.002) better correlated with subjective stress when compared to heart rate ( r = 0.30; P = 0.15). Agreement between raters for Anaesthetic Non‐Technical Skills (ANTS) scores was acceptable (ICC = 0.51; P = 0.003). Conclusion: This study suggests that higher patient ASA grade can increase stress in anaesthetists, which may impair non‐technical skills.